2015
DOI: 10.1186/s12875-015-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

Previous experiences and emotional baggage as barriers to lifestyle change - a qualitative study of Norwegian Healthy Life Centre participants

Abstract: BackgroundChanging lifestyle is challenging and difficult. The Norwegian Directorate of Health recommends that all municipalities establish Healthy Life Centres targeted to people with lifestyle issues. Little is known about the background, experiences and reflections of participants. More information is needed about participants to shape effective lifestyle interventions with lasting effect. This study explores how participants in a lifestyle intervention programme describe previous life experiences in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 36 publications
(39 reference statements)
7
41
0
Order By: Relevance
“…This is in line with many other studies showing that an optimal level of involvement depends on both users and professionals having adequate time to build relationships and share knowledge (Angel & Frederiksen, 2015; Leske, Strodl, & Hou, 2012; Rise et al, 2013; Sahlsten et al, 2009; Tobiano et al, 2015). On the other hand, the users’ often complex life challenges and conditions were described as a potential hindrance for user involvement, which is in accordance with other studies pointing out that users’ physical and mental capabilities, severe illness and poor health can impede involvement (Angel & Frederiksen, 2015; Longtin et al, 2010; Rise et al, 2013; Solbjør, Rise, Westerlund, & Steinsbekk, 2013; Tobiano et al, 2015) and health behaviour change (Abildsnes et al, 2017, 2016; Følling et al, 2015). In addition, our findings showed that the building of a trustful relationship and individualization of the service was disturbed by the use of standardized forms which interrupted the communication process.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in line with many other studies showing that an optimal level of involvement depends on both users and professionals having adequate time to build relationships and share knowledge (Angel & Frederiksen, 2015; Leske, Strodl, & Hou, 2012; Rise et al, 2013; Sahlsten et al, 2009; Tobiano et al, 2015). On the other hand, the users’ often complex life challenges and conditions were described as a potential hindrance for user involvement, which is in accordance with other studies pointing out that users’ physical and mental capabilities, severe illness and poor health can impede involvement (Angel & Frederiksen, 2015; Longtin et al, 2010; Rise et al, 2013; Solbjør, Rise, Westerlund, & Steinsbekk, 2013; Tobiano et al, 2015) and health behaviour change (Abildsnes et al, 2017, 2016; Følling et al, 2015). In addition, our findings showed that the building of a trustful relationship and individualization of the service was disturbed by the use of standardized forms which interrupted the communication process.…”
Section: Discussionsupporting
confidence: 85%
“…The HLCs are easily accessible, and people can attend the service through referral from a general practitioner (GP) or other health care providers or by self-referral (Norwegian Directorate of Health, 2016). The HLCs offers knowledge-based support for changing living habits and coping with health challenges through individual- and group-based counselling and activities, and use client-centred counselling approaches to promote the participants’ internal motivation, empowerment and coping (Abildsnes, Meland, Samdal, Stea, & Mildestvedt, 2016; Følling, Solbjør, & Helvik, 2015; Lerdal, Celius, & Pedersen, 2013; Norwegian Directorate of Health, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…50 The qualitative study that explored a segment of the same sample used in this study found that participants highlighted their surrounding resources as important to maintain healthy habits. 40 In light of our previous findings, 37 40 there may be a gap between the participants from the HUNT3 Survey presented in this study and those referred to lifestyle programs in the primary healthcare in Norway, in that the latter individuals may often already have developed different diseases related to their lifestyle choices. The previous and present results raise questions as to who benefits from lifestyle programs and highlight the importance of prevention programs at a population-based level, such as health promotion strategies that target all individuals.…”
Section: Epidemiology/health Services Researchmentioning
confidence: 62%
“…To date, much of the research on the experiences of people with obesity has focused on their experiences as recipients of health care for obesity .…”
Section: Introductionmentioning
confidence: 99%